Calving Pattern In Buffaloes, Indigenous And Crossbred Cattle In Anand And Kheda Districts Of Middle Gujarat - Patel, S.B.; Jethva , P.C. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Buffaloes are established seasonal breeders in India, while cattle show perennial breeding and calving pattern, however no comparative studies are yet available in the literature. Hence, Calving records of 12,816 graded Murrah buffaloes; 1,022 indigenous cattle and 10,264 crossbred cattle of 30 villages covered under Productivity Enhancement Programme (PEP) of Kheda and Anand districts of middle Gujarat attended over three years period were used to study and compare their calving pattern. The year was divided into four seasons, viz, summer (Mar to May), rainy/monsoon (Jun to Aug), autumn (Sept to Nov) and winter (Dec to Feb). The month and season had significant effect on calving pattern only in buffaloes. The highest calving frequency was noted in the month of October (17.24%) for buffaloes, in December for indigenous cattle (10.27%) and in January for crossbred (9.51%) cattle. The lowest calving were recorded for buffaloes in March (2.54%), and for indigenous (7.34%) and crossbred (7.08%) cattle in June. The highest calving frequency in buffaloes was observed during autumn season (45.91%), followed by winter (25.00%), rainy (20.50%) and summer (8.57%) seasons. However, no such distinct seasonality of calving was found in indigenous and crossbred cattle of the same region, although the highest calving frequency was recorded for indigenous cattle during winter (27.98%) and in crossbreds during autumn (26.66%), and the lowest percentages of calving were during the rainy season in both crossbreds (22.33%) and indigenous (23.68%) cattle. Seasonality of calving index (CI = ratio of number of calving in month with fewest calving and number of calving in month with most calving) was 85.29, 28.57 and 25.51 in buffaloes, indigenous and crossbred cattle, respectively. The results revealed that seasonality of calving is more pronounced in buffaloes than in indigenous and crossbred cattle of middle Gujarat.
Keywords: Calving Pattern; Middle Gujarat; Buffalo; Indigenous; Crossbred cow; Calving Index